2021
DOI: 10.1177/00207640211059678
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychosocial profile of persons with mental illness living in non-hospital residential facilities in a district in Kerala, India: A cross-sectional survey

Abstract: Background: Clinical and psychosocial profiles of persons living with mental illness (PMI) in non-hospital settings in India have not been adequately studied. Aim: This study describes the profile of PMI living in non-hospital settings by focussing on variables like functioning and social networks. Method: Residents of all available residential facilities in one district area were surveyed and descriptive data was obtained. Socio occupational functioning was assessed using the Social and Occupational Functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 9 10 12 14 ] The reasons that there were more males among the homeless persons could be because of financial difficulties, substance abuse, unemployment, and lack of social support. Studies from India and abroad[ 11 12 15 16 ] reported similar results in the socio-demographic variables, especially in unemployment, substance abuse, mental illness, inadequate support networks, and lack of affordable housing. This shows the general characteristics of street people both homeless persons with mental illness and homeless persons without mental illness.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…[ 9 10 12 14 ] The reasons that there were more males among the homeless persons could be because of financial difficulties, substance abuse, unemployment, and lack of social support. Studies from India and abroad[ 11 12 15 16 ] reported similar results in the socio-demographic variables, especially in unemployment, substance abuse, mental illness, inadequate support networks, and lack of affordable housing. This shows the general characteristics of street people both homeless persons with mental illness and homeless persons without mental illness.…”
Section: Discussionmentioning
confidence: 71%
“…To reduce functional disability and improve clinical outcomes, greater community integration of the homeless and mentally ill people is essential. [ 11 20 ] The current study suggests that psychosocial preparedness among HMI is the most significant aspect when considering independent housing or community living for HMI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…15 As part of a larger survey, the authors got an opportunity to visit and interact with the residents and facility managers of all residential facilities (n = 9) in one entire district area (Kollam district). 16 Almost all centers (n = 8) were registered as homes under the Orphanages and Other Charitable Homes (Supervision and Control) Act, 1960 17 Under this Act, the Orphanages Control Board supervises and controls all homes in the state, whether for the "differently-abled, beggars, women in distress, old age, or mentally ill persons. "…”
Section: Residential Facilities For Long-stay In Kerala Statementioning
confidence: 99%